USE OF ORGANOPHOSPHATED FERTILIZER AND FILTERCAKE IN PLANT-CANE - Vazquez, G. H.; Bortolin, R.; Vanzela, L. S.; Bonini, C. dos S. B.; Bonini Neto, A. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The aim of this work was to compare the effect of the use of organophosphated fertilizer and filtercake with mineral sources on biomass productivity, agronomic and technological characteristics of plant-cane and the economic return. The experiment was installed in Iturama/MG in a randomized blocks design with five repetitions, being the treatments: 1 = N-P-K (27, 135 and 108 kg ha-1 respectively), i.e. 450 kg ha-1 of the formula 6-30-24; 2 = N-P-K (60, 120 and 140 kg ha-1); 3 = N-P-K (14, 84 and 42 kg ha-1); 4 = 700 kg ha-1 organophosphated fertilizer (14, 70 and 70 kg ha-1 N-P-K); 5 = 700 kg ha-1 organophosphated fertilizer + 10 t ha-1 filtercake; 6 = N-P-K (27, 135 and 108 kg ha-1) + 10 t ha-1 filtercake; 7 = N-P-K (60, 135 and 108 kg ha-1); 8 = 10 t ha-1 filtercake + 108 kg ha-1 K; 9 = 10 t ha-1 filtercake + N + K (27 and 108 kg ha-1) and 10 = 10 t ha-1 filtercake + N-P-K (30, 50 and 110 kg ha-1). It was concluded that the various levels and sources of phosphorus studied did not affect the biomass productivity of the plant-cane; the filtercake provided a smaller percentage of failures of stalks in sugar cane line and the highest economic return was obtained by the joint use of filtercake and organophosphated fertilizer in plant-cane.